Membangun Jiwa Kewirausahaan melalui Pelatihan dan Pendampingan Kewirausahaan bagi Anak-anak Panti Asuhan ‘Aisyiyah Nur Fauzi - Nurul Aini, Khadijah; Saleh, Mustaruddin; Agustina, Devita; Natalie, Gabriella; Sal Sabila, Aulia; Rizky Ananda Putri, Gita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This community service activity is motivated by a problem, specifically the lack of entrepreneurial experience in orphanage children. Entrepreneurial activity is an important factor in improving community welfare. In accordance with the vision and mission of ‘Aisyiyah Nur Fauzi Orphanage, which is to train orphanage children to become independent, this entrepreneurial service activity is in line with the vision and mission. But in reality, the experience of orphanage children in entrepreneurship is very limited due to the lack of facilities owned. The implementation of this series of activities using lecture and practice methods. This service activity involves orphanage children through training and mentoring in entrepreneurial activities, starting from introducing entrepreneurship, practicing making business products for accessories and spring rolls, designing posters and logos, promotion, determining capital and setting price, selling and marketing the products they made to consumers. The results of this service activity provide new knowledge and experience in entrepreneurship for orphanage children so that they gain new experiences regarding entrepreneurial training. This service is expected to have a positive impact in an effort to create a young generation that has entrepreneurial knowledge and skills, and can make a creative and innovative person to face obstacles in the future.